Afghanistan Development Update, May 2017 - World Bank (Washington, DC, 2017)
The Afghanistan Development Update, which is published twice a year, provides a comprehensive report of the state of the Afghan economy. It covers recent economic developments and outlines the medium-term outlook for Afghanistan. Afghanistan. Each edition includes a section that provides in-depth analysis on one or more specific focus topics. The lack of high-frequency data in Afghanistan makes it difficult to track economic activities on a monthly or quarterly basis. Thus, proxy indicators are utilized when their quality is deemed satisfactory. Efforts are made to ensure that key analysis and forecasts are based primarily on reliable sets of data. The Afghanistan Development Update is intended for a wide audience, including policy makers, the donor community, the private sector, the community of analysts and professionals engaged in monitoring the economy and Afghanistan’s citizens at large. In this issue of the Update, the Focus Section discusses how economic stimulus can be provided in Afghanistan’s resource-constrained environment. In the context of the economic slowdown, Afghanistan faces the difficult dilemma of balancing measures to stimulate the economy while at the same time avoiding a further weakening of its fiscal position. The fiscal space is already extremely limited, with no room to increase public expenditure or to lower taxes. Thus, the Government must implement initiatives to maximize the growth impact of fiscal expenditure. First, policies to encourage government spending on non-tradable goods from local suppliers will ensure that demand taps domestic production, rather than imports. Second, policies to improve absorptive capacity will increase the quality, speed of execution and value for money of public investments. Third, policies to promote contestable markets in banking and construction will stimulate the entry of small and medium-sized firms in both sectors. Fourth, polices to increase fiscal space should include measures to improve revenue mobilization and to use existing resources more effectively, which will release additional resources.